Роман с Хаосом - Мартьянов Андрей (Галактический патруль, 2002)
Экземпляры: Ф. 8 (20200814) / Инвентарный номер: 46172 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 29 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6